Central venous catheters do not increase the hemorrhagic risk in acute promyelocytic leukemia patients during induction therapy - Cao, Manxiong; Hong, Jiaqiong; Zhang, Dongqing; Chen, Feiheng; Su, Yongzhong (Frontiers in Oncology, 2024)
In acute promyelocytic leukemia (APL), hemorrhage, particularly intracranial hemorrhage, is the most common cause of early death. A central venous catheter (CVC) may provide a greater guarantee of safety and comfort to APL patients. However, CVCs have seldom been attempted in APL patients during induction therapy because of concerns about increasing the risk of hemorrhagic complications after this invasive procedure. To evaluate the hemorrhagic risk after CVC placement in APL patients during induction therapy, we retrospectively analyzed 95 newly diagnosed patients with APL from January 2010 to December 2022. Among these patients, 39 patients in the CVC group and 56 patients in the non-CVC group were included. Laboratory and clinical parameters of the two groups were collected and compared. There were no significant differences in median platelet, fibrinogen (Fbg), D-dimer, prothrombin time (PT), white blood count (WBC) and hemoglobin (Hb) between the CVC and non-CVC groups on the first day of the visit (day 0) and the following days (day 4, day 7, day 11, day 14, day 18 and day 21) (p = 0.382, p = 0.805, p = 0.456, p = 0.902, p = 0.901 and p = 0.097, respectively). The consumption of transfused platelets and Fbg was not significantly different between the CVC group and non-CVC group (5.0 vs. 4.5 units, p = 0.34, and 6.8 vs. 6.0, p = 0.36, respectively). The last day of platelet and Fbg transfusion was also not significantly different (21 vs. 19, p = 0.238 and 7.5 vs. 8.5, p = 0.684, respectively). The incidences of total hemorrhagic events and hemorrhagic death were lower in the CVC group than in the non-CVC group (17.9% vs. 37.5%, p = 0.04 and 0% vs. 16.1%, p = 0.01, respectively). The 30-day survival rate was not significantly different (92.3% vs. 82.1%, respectively, p = 0.145) for the CVC group compared with the non-CVC group. Our study suggested that CVCs did not increase the hemorrhagic risk in APL patients during induction therapy and that a CVC should be considered in this type of clinical situation.